A colour normalization method for Giemsa-stained blood cell images - Tek, F. Boray; Dempster, Andrew G.; Kale, Izzet (IEEE, 2006)
This paper presents a novel method for the colour normalization of Giemsa-stained peripheral blood cell images. The normalization is applied separately to the foreground and background regions. A rough estimation of the foreground-background regions is done by mathematical morphology and followed by a refined segmentation using histograms of these regions. Then an illumination independent response is calculated using the background region. The normalization is completed by transforming the foreground region according to a reference set. The proposed method has been tested on many images and has been found successful.
IEEE 14th Signal Processing and Communications Applications -- APR 16-19, 2006 -- Antalya, TURKEY